Development of a Discharge Criteria Checklist for COVID-19 Patients From the Intensive Care Unit. Issue 2 (April 2023) - Mahran, Ghada S. K.; Gadallah, Marzoka A.; Ahmed, Awatef E.; Abouzied, Warda R.; Obiedallah, Ahmed A.; Sayed, Magdy M. M.; Abbas, Mostafa S.; Mohamed, Sherif A. A.
Abstract : This study aims to develop and validate a checklist of discharge readiness criteria for COVID-19 patients from the intensive care unit (ICU). We conducted a Delphi design study. The degree of agreement among 7 experts had been evaluated using the content validity index (CVI) through a 4-point Likert scale. The instrument was validated with 17 items. All the experts rated all items as very relevant which scored the item-CVI 1, which validates all checklist items. Using the mean of all items, the scale-CVI was calculated, and it was 1. This meant validation of the checklist as a whole. With regard to the overall checklist evaluation, the mean expert proportion of the instrument was 1, and the S-CVI/UA was 1. This discharge criteria checklist improves transition of care for COVID-19 patients and can help nurses, doctors, and academics to discharge COVID-19 patients from the ICU safely.